A Prospective, Randomized, Blinded, Placebo‐Controlled Pilot Study on the Effect of Enterococcus faecium on Clinical Activity and Intestinal Gene Expression in Canine Food‐Responsive Chronic Enteropathy. (16th March 2015) - Schmitz, S.; Glanemann, B.; Garden, O.A.; Brooks, H.; Chang, Y.M.; Werling, D.; Allenspach, K.
Abstract : Background: Canine chronic enteropathies (CE) are believed to be caused by an aberrant immune response towards the intestinal microbiome. Administration of probiotics can alleviate colitis in people. In vitro effects of the probiotic Enterococcus faecium NCIMB 10415 E1707 (EF) previously have been evaluated using canine cells (e.g., whole blood, intestinal biopsies), but data on in vivo efficacy are lacking. Hypothesis/Objectives: Administration of EF to dogs with food‐responsive CE will improve clinical outcome and decrease the intestinal inflammatory profile. Animals: Dogs diagnosed with CE were prospectively recruited to receive a hydrolyzed elimination diet plus either a synbiotic product containing EF or placebo for 6 weeks. Both veterinary staff and owners were blinded to the treatment. Methods: Clinical severity index (CCECAI), clinicopathological data and gene expression using intestinal biopsies (TLR2/4/5/9, IL‐17A, IL‐22, IL‐23p19, RORC, IL‐2, IL‐12p35, TNFα, IL‐4, IFNy, IL‐10, TGFβ, IL‐1β, IL‐18, NLRP3, casp‐1, TFF1, TFF3 and PPARy) before and after 6 weeks of treatment were analyzed using linear mixed modeling. Results: Of the 45 cases recruited, 12 finished the clinical trial. Seven received the synbiotic and 5 the placebo product. There was no difference between groups or treatments regarding clinical efficacy, histology scores or expression of any of the investigated genes. Conclusions and clinical importance: Standard dietary treatment induced rapid clinical response in all cases. Because the study was underpowered, it was not possible to determine whether or not EF had an additional effect within the time period of 6 weeks.